PERSEPSI PENGRAJIN BATIK TENTANG PENERAPAN SELF-HELP GROUPS DALAM RANGKA PENGUATAN SENTRA INDUSTRI BATIK - Dewi Prihatini (RELASI : JURNAL EKONOMI, 2013)
The study aims to analyze the perception of the batik craftmen  toward self-help groupsthat had been advocated for development and strengthening the center of the batik industry in Tuban District.This study is a descriptive research. The respondents were determined by snowball sampling method consisting of 84 batik craftmen  in the batik industry.  Both qualitative and quantitative research approaches were used  in this study. Aside from the secondary data, the primary data was collected by ethnographic (unstructured and semi-structured interviews, and direct observation) and participatory methods (key informant interviews).The result  of the study shows  that  the perception of the batik craftmen toward the contribution of self-help groups  for development and strengthening the center of the batik industry in  Tuban District  is categorized “moderate”.  Therefore, improvement in the aspects of  raw materials supply, technology applied, and business management in  the  business performance  of batik  industries  are still needed.